Correlation between Autorefractometry and Retinoscopy with Subjective Refraction in Refractive Error Patients at Dr Kariadi Hospital, Semarang - Disti Hardiyanti; Fatimah Dyah NA (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Objective: Refractive errors are a major cause of visual impairment in Indonesia. In Dr. Kariadi Hospital Semarang, it is amongst the top five diagnoses within the ophthalmology department. Therefore, objective refraction is imperative for the management of refractive errors. These examinations include autorefractometry and retinoscopy. Despite the fact that retinoscopy is the gold standard, autorefractometry is more desirable as it is more sophisticated, swift, and convenient. Autorefractometry's results are expected to match results from subjective correction, therefore, reduce examination time as patient visits increase. This study aims to determine the correlation between autorefractometry and retinoscopy examination with subjective refraction. Methods: The study design was cross-sectional. The study was conducted on 34 eyes with refractive error taken by consecutive sampling. The subjects had to meet inclusion and exclusion criteria. All subjects underwent visual acuity examination, refractive correction by autorefractometry, retinoscopy, and subjective refraction. All data were processed by using computerized formulations. Results: Based on the demographics there were 61.8% of women and 38.2% of men with an average age of 29.7 + 9. The results of this study showed a strong correlation between autorefractometry and subjective refraction. Furthermore, retinoscopy shows a strong correlation with subjective refraction as well. Conclusion: This study shows retinoscopy is superior to autorefractometry. However, autorefractometry is a viable replacement for patients in Dr. Kariadi Hospital Semarang.